An examination of how individuals experience a traumatic bond: a latent profile analysis expanding traumatic bonding theory - Palmer , Megan (Kansas State University, 2024)
This study examines the facets of trauma bonding as initially outlined by Dutton and Painter (1981) to deepen our understanding of this phenomenon. These facets include intermittent reinforcement/punishment, love dependence, self-blame, low self-esteem, power imbalance, anxious attachment, and avoidant attachment. Data were collected from 510 individuals currently in romantic relationships via the online platform Prolific. Utilizing latent profile analysis (LPA), a four-class model emerged as the best fit, delineating the following classes: (a) high anxious attachment (b) probable trauma bond, (c) no trauma bond, and (d) high intermittency. I also utilized path analysis to identify if there were significant relationships between facets of trauma bonding and various types of IPV (e.g., physical, psychological, sexual, severe). Importantly, high self-esteem and anxious attachment did not have a significant relationship with any types of IPV, while love dependence, intermittent reinforcement and punishment, self-blame, and power had a relationship with at least one form of IPV. As well These findings highlight diverse experiences of traumatic bonding within our sample, suggesting the necessity for further exploration of these facets in future research.
Keywords: Intimate partner violence; Trauma bonding; Latent profile anlaysis; Odds ratio